2018
DOI: 10.1080/11356405.2018.1457610
|View full text |Cite
|
Sign up to set email alerts
|

Teaching methodologies at university and their relationship with the development of transversal competences / Metodologías de enseñanza en la universidad y su relación con el desarrollo de competencias transversales

Abstract: This paper aims to understand the use of different methodologies and their relationship with the development of transversal competencies within higher education. A total of 1,137 final-year undergraduate students from the University of Murcia participated in this study, and the data collection instrument used is the CECTGRA questionnaire designed ad hoc. Among the most noteworthy results is the prevalence of lectures compared with other more active methodologies and the perception that the development of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
7
0
4
Order By: Relevance
“…Robledo Ramón et al (2015) conducted a comparative analysis of the impact of five active teaching-learning methods (project-based learning, case studies, shared study, directed study and expert method) in acquiring competences in a cohort of 280 higher education students and concluded that of all the methodologies analysed, PBA is the one that contributes the most to helping university students develop instrumental, systemic and interpersonal competence. In this sense, Martínez-Clares and González-Morga (2018) studied the relationship between the use of different teaching methodologies and the development of transversal competences in university education, and they found that the higher the use of the project-based learning method, the higher the students' perception of having acquired this type of competence. Chen and Yang (2019) define PBA as a student-centred teaching-learning methodology in which the students, organized into working teams, address a real problem to try to provide a solution, guided by an instructor (Servant-Miklos, 2019).…”
Section: Project-based Learning and Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Robledo Ramón et al (2015) conducted a comparative analysis of the impact of five active teaching-learning methods (project-based learning, case studies, shared study, directed study and expert method) in acquiring competences in a cohort of 280 higher education students and concluded that of all the methodologies analysed, PBA is the one that contributes the most to helping university students develop instrumental, systemic and interpersonal competence. In this sense, Martínez-Clares and González-Morga (2018) studied the relationship between the use of different teaching methodologies and the development of transversal competences in university education, and they found that the higher the use of the project-based learning method, the higher the students' perception of having acquired this type of competence. Chen and Yang (2019) define PBA as a student-centred teaching-learning methodology in which the students, organized into working teams, address a real problem to try to provide a solution, guided by an instructor (Servant-Miklos, 2019).…”
Section: Project-based Learning and Entrepreneurshipmentioning
confidence: 99%
“…Robledo Ramón et al (2015) realizan un análisis comparativo sobre impacto de cinco métodos de enseñanza aprendizaje activos (Aprendizaje basado en Proyectos, Estudio de casos, Estudio compartido, Estudio dirigido y Método de expertos) en la adquisición de las competencias de un grupo de 280 estudiantes de Educación Superior concluyendo que el ABP es, de todas las metodologías analizadas, la que más contribuye al desarrollo de competencias instrumentales, sistémicas e interpersonales en el alumnado universitario. En este sentido, Martínez-Clares y González-Morga (2018) estudian la relación entre el uso de diferentes metodologías de enseñanza y el desarrollo de las competencias transversales en la formación universitaria y obtienen que cuanto mayor es el uso de del método de aprendizaje por proyectos mayor es la percepción de la adquisición de este tipo de competencias entre los estudiantes.…”
Section: Aprendizaje Basado En Proyectos Y Emprendimientounclassified
“…An education in which the development of competencies is especially present. The different phases of the process drive the development of key competencies that are vital for students while being underrepresented in current university curricula [55][56][57][58]. The method's most important contribution is its ability to develop the creativity of students, as well as their interest in undertaking projects and providing original, unique and authentic solutions, as reflected in other research [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Habilidades como a criatividade, inovação, inteligência interpessoal, administração de conflitos, trabalho em equipe, entre outras características, atuam como diferencial dos profissionais que se formam e passam a atuar (URIAS; AZEREDO, 2017). Surge uma concepção de ensino centrada não mais no professor, mas com o foco no aluno, e este com capacidade para avançar na sua aprendizagem de forma autônoma e ativa, provocando questionamentos sobre como e porque ensinar (MARTÍNEZ-CLARES; GONZÁLEZ-MORGA, 2018).…”
Section: Metodologias Ativas E Suas Abordagensunclassified